Relevance of Ayurveda Management in Duchenne Muscular Dystrophy to Augment the Quality of Life- A Pediatric Case Report: Life Sciences -Ayurveda - Rathi, Renu; Shirbhate, Sakshi; Rathi, Bharat; Misar, Sadhana; Kurhadkar, Monali; Yewle, Prasad (International Journal of Life Science and Pharma Research, 2023)
Muscular dystrophy is a myopathy that stakes clinical characteristics of progressive muscular feebleness. Duchenne muscular dystrophy (DMD) is the most common X-linked disorder of muscular dystrophy in children, present in early childhood, and characterized by proximal muscle weakness and calf hypertrophy in affected boys. This case aims to make Ayurveda pediatricians aware of planning a protocol for DMD. The objective is to provide instant relief in motor function to some extent and to augment the quality of life. An 11 years old boy was presented with an in ability to stand, gross muscle weakness, difficulty in movements of lower limbs, and particularly in all vigorous physical activities. He also had decreased strength, stamina, and progressive debility with positive Gower’s sign, which suggested DMD. Confirmed economic treatment options are unavailable to prevent progressive illness and mortality. The family members were counselled and assured of improving their quality of life. He was started with multiple pre-panchakarma procedures of alternate Rukshan and Brihan to pacify internal Ayurveda medicines with the support of occupational therapy and physiotherapy in different sittings for three months. His CPK -creatinine kinase was 8335 U/L (NV= 55 to 170 U/L) which became4741U/L post-treatment. He could stand with support for 15 minutes on his own with ease in body movements due to a reduction in contractures & increase in the range of motions measured by the goniometer, as this genetic disease has no medicinal cure. However, by adopting a multi-dimensional integrative approach, family support, and willpower, the quality of life can be augmented to much extent. Ayurveda plays a crucial role in the drastic improvement because of panchkarma shaman procedures, medicines, Yog, physiotherapy, traction, and counselling at regular intervals for lifelong.